Kisah Ashḥāb Al-Ukhdūd dalam Al-Qur’an: Tinjauan Antropologi - Muhammad Zulfikar Nur Falah (Studia Quranika, 2024)
The stories in the Koran are told in whole in one location, but they are sometimes told in fragments over numerous surahs. The story of ashḥāb al-ukhdūd is only told in QS. al-Buruj [85]: 4-9 at once not scattered in several surahs. The reason for the study is based on contextualization related to anthropology because the story of ashḥāb al-ukhdūd has involved agents in creating culture as a result of interpersonal relationships. The formulation of the problem in this study is how the story of ashḥāb al-ukhdūd in the Koran and its contextualization is related to anthropology. This study uses the library research method, with relevant and reliable sources, such as books, journals, theses, dissertations, etc. Answering the formulation of the problem, this research gives the result that the story of ashḥāb al-ukhdūd in the Koran, tells of the killing of Dzu Nuwas and his followers who had tortured the Christian population of Najran. In terms of contextualization related to anthropology, it implicitly contained power fanaticism as the heir to the customs, attitudes, and behavior of the main figure of ashḥāb al-ukhdūd, namely Dzu Nuwas and his followers. Their two lifestyle entities are against the apostleship of Prophet Isa As. along with its people and prioritize confrontational attitudes so as not to be surpassed by the existence of beliefs that have long been believed